2016
DOI: 10.1177/1742271x16673677
|View full text |Cite
|
Sign up to set email alerts
|

Value of ultrasound shear wave elastography in the diagnosis of adenomyosis

Abstract: This study showed a significant increase of the myometrial stiffness estimated with shear wave elastography use in patients with adenomyosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…Their results supported the capability of strain elastography to differentiate adenomyosis from leiomyomas, although 1 study showed suboptimal agreement between strain elastography diagnosis of adenomyosis and histology . Only 1 study in the literature used SWE to evaluate adenomyosis, with results similar to ours: significantly increased myometrial stiffness in patients with adenomyosis. The above‐mentioned inconsistency might reflect underlying technical differences in measuring tissue stiffness within a confined organ, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Their results supported the capability of strain elastography to differentiate adenomyosis from leiomyomas, although 1 study showed suboptimal agreement between strain elastography diagnosis of adenomyosis and histology . Only 1 study in the literature used SWE to evaluate adenomyosis, with results similar to ours: significantly increased myometrial stiffness in patients with adenomyosis. The above‐mentioned inconsistency might reflect underlying technical differences in measuring tissue stiffness within a confined organ, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 65%
“…Several recent studies use strain elastography to diagnose adenomyosis and uterine leiomyomas . Only 1 study in the literature investigates SWE of adenomyosis . Thus, the use of in vivo SWE for myometrial assessment is truly a novel application of an emerging technology.…”
mentioning
confidence: 99%
“…In contrast, adenomyosis impairs the function of the myometrium. A recent report showed a significant increase in the myometrial stiffness (estimated with shear wave elastography) in patients with adenomyosis . In fact, the intrauterine pressure has been reported to be increased in pregnant women with adenomyosis .…”
Section: Discussionmentioning
confidence: 98%
“…A recent report showed a significant increase in the myometrial stiffness (estimated with shear wave elastography) in patients with adenomyosis. 18 In fact, the intrauterine pressure has been reported to be increased in pregnant women with adenomyosis. 7,19 The uterine contractions caused by chronic inflammation and a high intrauterine pressure caused by myometrial stiffness might be factors that contribute to adenomyosis-related miscarriage and cervical incompetency.…”
mentioning
confidence: 99%